RETRACTED: The significance of queen bee eggs in beekeeping (in the conditions of Bukhara region) - Azizova N.A.; Torayev M.M.; Bakayeva Sh.B.; Ghaziyeva G.A. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001